2017
DOI: 10.1186/s13099-017-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of antidiarrhoeal effects by diosmectite in human intestinal cells

Abstract: BackgroundRotavirus (RV) induces diarrhoea through a sequence of enterotoxic and cytotoxic effects. The former are NSP4-dependent, induce calcium-dependent chloride secretion and involve oxidative stress. Diosmectite (DS) is a natural clay that has been recommended as an active therapy for diarrhoea, but the mechanism of its effect is not clear. Electrical parameters may be used to measure the direct enterotoxic and cytotoxic effects in polar epithelial intestinal cells. To investigate the effects of DS on RV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…Although the mechanism of action of smectite is not clearly understood, it is an activated natural aluminosilicate clay that can adsorb water and presents multiple other interesting properties: it prevents toxins, bacteria and viruses adhering to intestinal membranes, 9,13‐17 it has been shown to strengthen the mucosal barrier in vitro and in vivo, 18‐20 to have some anti‐inflammatory properties, 17,18,21,22 to decrease intestinal bacterial translocation 23 and to stabilize the intestinal microbiome 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of action of smectite is not clearly understood, it is an activated natural aluminosilicate clay that can adsorb water and presents multiple other interesting properties: it prevents toxins, bacteria and viruses adhering to intestinal membranes, 9,13‐17 it has been shown to strengthen the mucosal barrier in vitro and in vivo, 18‐20 to have some anti‐inflammatory properties, 17,18,21,22 to decrease intestinal bacterial translocation 23 and to stabilize the intestinal microbiome 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…They suggest that this ability to remove (adsorb) bacterial toxins is one of the possible mechanisms of its therapeutic action. Other possible mechanisms of the therapeutic action of enterosorption include immunocorrection 31 , creation of an unfavourable environment for pathogenic microorganisms 32 , and inhibiting viral replication 33 however, in all cases the primary action is physical adsorption. For Enterosgel, the adsorption of molecules occurs via the diffusion of molecules within the three-dimensional polymer network filled with water and their retention by the polymer chains.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies have demonstrated Enterosgel’s capacity for Escherichia coli endotoxin, bacterial enterotoxins Clostridium difficile toxin A and B, and Shigella toxin16 and staphylococcal enterotoxins A and B 17. Other mechanisms may include creation of an adverse environment for pathogenic microorganisms,18 immunocorrection19 and inhibiting viral replication,20 primarily through physical adsorption. A possible benefit of Enterosgel use is in reducing the level of complications of diarrhoea-related bacterial infection.…”
Section: Discussionmentioning
confidence: 99%